2022
DOI: 10.1097/qad.0000000000003432
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes associated with combination antiretroviral therapy compared with monotherapy

Abstract: Objectives: Increasing numbers of women living with HIV (WLHIV) worldwide receive combination antiretroviral therapy (cART) during pregnancy. We aimed to assess the risk of adverse perinatal outcomes in pregnant WLHIV receiving cART compared with pregnant WLHIV receiving zidovudine monotherapy.Design: Systematic review and meta-analysis.Methods: We searched four electronic literature databases (PubMed, CINAHL, Global Health, EMBASE) for studies published between 1 January 1980 and 20 April 2020 using a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Recent metanalyses and systemic review of Sub-Saharan African cohorts and RCT data have shown that preconception and antenatal triple ART are associated with PTB, low birth weight and small for gestational age babies in women living with HIV compared to those receiving ZDVm and to uninfected women [ 59 ]. It is possible that the continued association of triple ART with adverse birth outcomes may be drug specific, with another large meta-analyses from the same group demonstrating that compared with ZDVm, non-nucleoside reverse transcriptase inhibitor-based triple ART was associated with an increased risk of PTB, LBW, and stillbirth, and PI-based triple ART with PTB [ 60 ]. Increasing safety data for ART in pregnancy has resulted in more ART choices for pregnant women including Integrase Stand Transfer Inhibitors, with Dolutegravir now a preferred third drug in many international pregnancy guidelines due to its efficacy, reassuring safety profile and fewer drug interactions [ 28 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent metanalyses and systemic review of Sub-Saharan African cohorts and RCT data have shown that preconception and antenatal triple ART are associated with PTB, low birth weight and small for gestational age babies in women living with HIV compared to those receiving ZDVm and to uninfected women [ 59 ]. It is possible that the continued association of triple ART with adverse birth outcomes may be drug specific, with another large meta-analyses from the same group demonstrating that compared with ZDVm, non-nucleoside reverse transcriptase inhibitor-based triple ART was associated with an increased risk of PTB, LBW, and stillbirth, and PI-based triple ART with PTB [ 60 ]. Increasing safety data for ART in pregnancy has resulted in more ART choices for pregnant women including Integrase Stand Transfer Inhibitors, with Dolutegravir now a preferred third drug in many international pregnancy guidelines due to its efficacy, reassuring safety profile and fewer drug interactions [ 28 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the largest numbers of studies and WLHIV in our analyses, compared to other perinatal outcomes assessed. However, it remains the case that WLHIV receiving ART are at higher risk of PTB compared to WLHIV receiving ZDV monotherapy and HIV-negative women ( 11 , 58 ). Our findings indicate that choice of ART regimen does not impact the elevated risk of PTB among pregnant WLHIV and hence other interventions are urgently needed to reduce the burden of PTB among WLHIV.…”
Section: Discussionmentioning
confidence: 99%